Carbapenem-resistant bacteria on hand-held and hands-free electronic devices of healthcare workers and non-healthcare workers in Delhi, India. Issue 3 (September 2021) - Bhalla, Manpreet; Aggarwal, Amit; Fatima, Khan Hena
Summary: Background: Monitoring sensitivity profiles of circulating hospital strains is a key activity of a hospital infection control policy. The hospital environment and equipment may be reservoirs for carbapenem-resistant bacteria. Mobile phones have been shown to be a potential source for the transmission of bacteria in the healthcare environment. Methods: Bacteria were cultured from seven common electronic devices. These included touchpads, chargers, hands-free headphones/microphones, laptops, digital wristwatches and computer mice which were used by healthcare workers and non-healthcare workers including family members and patient attendants. The Gram-negative bacteria were further analysed for phenotypic and genotypic ( bla KPC, bla NDM-1 genes) carbapenem resistance. Results: 110 Gram-negative bacteria were isolated Mobile phones were found to be the most heavily contaminated devices and hands-free devices the least. 53.6% (n=59/110) Gram-negative bacteria were phenotypically carbapenem-resistant of which 36.37% (n=40) were metallo-β-lactamase positive. 40% (n=44/110) were genotypically resistant and 30% (n=33) were bla NDM-1 gene positive. 9% (n=10) bacteria had both bla NDM–1 and bla KPC genes. Conclusions: Carbapenem-resistant bacteria are widespread in India's hospital environment and present a challenge in healthcare. Electronic devices are a potential vehicle for the transmission of carbapenem-resistant bacteria. The results of the study support that hands-free electronic devices are less likely to be contaminated with carbapenem-resistant bacteria and that promoting the use of hands-free devices may help to reduce the spread of multidrug resistant bacteria in healthcare.